(untitled) - Lammle, Todd (Indianapolis, 2006)
From bestselling author Todd Lammle comes the most up-to-date book on CCNA exam 640-821, the first exam in Cisco's popular two-exam Cisco Certified Network Associate (CCNA) certification track. Understand networking for the small or home office market, prepare for the exam, and acquire the skills you need with this comprehensive guide.
Keywords: Electronic data processing personnel,Computer networks,Xử lý dữ liệu chuyên nghiệp,Mạng máy tính; Certification,Examinations,Chứng chỉ,Kiểm tra